A new species of Metelasmus (Diptera: Streblidae: Streblinae) from southern South America - Graciolli, Gustavo; Dick, Carl W. (Zootaxa, 2004)
A new species of Metelasmus Coquillett, 1907 (Diptera: Streblidae: Streblinae) from Sturnira lilium (E. Geoffroy, 1810) (Chiroptera: Phyllostomidae: Stenodermatinae) is described. Drawings of the frontoclypeus, epiproct, gonopods, postgena, postvertex and occiputs, tergite VII, and wing are presented. Host relationships of Metelasmus are discussed.